2013
DOI: 10.4049/jimmunol.1203435
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor A Modulates the Immune Response to Pulmonary Cryptococcus neoformans Infection

Abstract: Scavenger receptors represent an important class of pattern recognition receptors shown to mediate both beneficial and detrimental roles in host defense against microbial pathogens. The role of the major macrophage scavenger receptor, scavenger receptor A (SRA), in the immune response against the pathogenic fungus, Cryptococcus neoformans, is unknown. To evaluate the role of SRA in anticryptococcal host defenses, SRA+/+ mice and SRA−/− mice were infected intratracheally with C. neoformans. Results show that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 49 publications
2
38
2
Order By: Relevance
“…In contrast, Ssa1 directly modulates macrophage- C. neoformans interactions only during the innate phase, with little to no effect on the development of adaptive immunity. In an attempt to specifically address the mechanism of Ssa1-dependent effects on macrophages, our laboratory has performed studies using mice deficient in the SRA receptor, which we originally thought to be the major receptor for the Ssa1 protein (53). Through our investigation, we have found that it is possible that some effects of Ssa1 on macrophages could be induced by SRA; however, the data were not very clear, hinting that multiple receptors and signaling pathways were likely to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ssa1 directly modulates macrophage- C. neoformans interactions only during the innate phase, with little to no effect on the development of adaptive immunity. In an attempt to specifically address the mechanism of Ssa1-dependent effects on macrophages, our laboratory has performed studies using mice deficient in the SRA receptor, which we originally thought to be the major receptor for the Ssa1 protein (53). Through our investigation, we have found that it is possible that some effects of Ssa1 on macrophages could be induced by SRA; however, the data were not very clear, hinting that multiple receptors and signaling pathways were likely to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Our data shows that sustained IL-10 production plays a central role in determining this balance during both the developing and established phases of infection. Numerous Cryptococcal virulence strategies are associated with increased expression of IL-10 including expression of its polysaccharide capsule, laccase, and its interference with macrophage scavenger receptor A (14, 26, 5356), showing that C. neoformans can exploit the IL-10 signaling pathway to oppose protective effector mechanisms. Importantly, the current study illustrates our ability to block this regulatory pathway, thereby restoring and potentially enhancing protective immune effector mechanisms which improve fungal clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Using an in vitro shRNA screen of mouse macrophages during cryptococcal stimulation, Means et al demonstrated that the scavenger receptors CD36, SCARF1 and SCARB2 promote IL-1β generation and are protective during cryptococcal immune responses [129]. Conversely, studies using Scavenger Receptor A (SRA)-deficient mice demonstrated that SRA signaling contributed to nonprotective immunity via decreased DC and CD4 + T-cell accumulation, decreased DC1 polarization and an increase in the hallmarks of nonprotective immune responses including eosinophilia and IL-10 production [130]. This suggests that C.neo exploits SRA to modulate the host response, promoting responses that favor survival and persistence of the microbe.…”
Section: Dcs As Gatekeepers: Pathogen Recognition and Dendritic Cell Acmentioning
confidence: 99%